C2/c-C32: A New Superhard sp^3 Carbon Allotrope with Direct Band Gap - Yao, R.; Jia, X.; Zhu, X.; Zhang, M.; Wei, Q. (Acta Physica Polonica A, 2023)
A new monoclinic carbon crystal with the space group C2/c was uncovered; its unit cell comprises 32 carbon (C32) atoms. This full sp3-bonded carbon phase is dynamically and mechanically stable. The results show that C2/c-C32 has excellent mechanical properties, with its shear modulus and Vickers hardness being 343 and 56 GPa, respectively. Based on the elastic anisotropic calculations, C2/c-C32 is confirmed to be an anisotropic material. Notably, C2/c-C32 has a direct band gap structure with a band gap of 2.50 eV.